Investigation on the dynamic stability of an underwater glider using CFD simulation - Javaid, M.Y. (Institute of Electrical and Electronics Engineers Inc., 2017)
Dynamic stability is an important consideration for an underwater glider because its slow motion makes it susceptible to underwater currents. This is compounded by its weak propulsion system whereby it self-propels by shifting its net buoyancy either positive or negative during forward motion. In this paper, steady state Computational Fluid Dynamic (CFD) simulation was used to evaluate the dynamic stability of a low-speed underwater glider. Fluid domains were generated for different flow velocities and angles of attack, for both rectilinear and rotary motions. For rectilinear motion, a straight line resistance test was replicated the tow tank resistance test. For rotary motion, a rotating arm setup was replicated and various angular velocities were numerically simulated. Hydrodynamic derivatives were obtained by extracting the slopes of the lift force and moment data points. The results showed that the dynamic stability of glider improved as the velocity and mass of the glider increases. © 2016 IEEE.